PENGARUH LAYANAN INFORMASI PENDIDIKAN SEKS TERHADAP PENGETAHUAN SISWA TENTANG SEKS KELAS VIII SMPN - Citrawati, Neka; Yuline, Yuline; Endang, Busri (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
Abstract This study aims to find out more about how big the influence of sex education information services to students' knowledge about sex in class VIII SMPN 1 Matan Hilir Selatan. The form of this study is the study of relationships. The sample of this research is class VIII students. Data collection techniques used is indirect kominaksi technique in the form of questionnaire amounted to 47 questions on the variables of sex education information services and 47 questions on the student's knowledge variable about sex. Based on the results of data analysis shows that sex education information service reached 90.33%. included in either category. While students' knowledge of sex reached 89.7% in either category. Based on the amount of contribution of information service of sex education to student knowledge about sex is 55.22%, it means 44.78% of students' knowledge about sex is influenced by other variables not obtained in this research. Keywords: Sex Education Information Service, Sex Knowledge